Learning to Estimate 3D Human Pose from Point Cloud - Zhou, Yufan (Université d'Ottawa / University of Ottawa, 2020)
As the development of the health and well-being industry advances, the importance of maintaining physical exercise on a regular basis should not be understated. To help people evaluate their pose during exercise, pose estimation has aroused massive interest among researchers from various fields. Meanwhile, pose estimation, especially 3D pose estimation, is a challenging problem in computer vision. Although substantial progress has been made over the past few years, there are still some limitations, such as low accuracy and the lack of comprehensive and challenging datasets for use and comparison. In this thesis, we study the task of 3D human pose estimation from depth images. Different from the existing CNN-based human pose estimation method, we propose a deep human pose network for 3D pose estimation by taking the point cloud data as input data to model the surface of complex human structures. We first cast the 3D human pose estimation from 2.5D depth images to 3D point clouds and directly predict the 3D joint positions. Our proposed methodology combining a two-stage training strategy is crucial for pose estimation tasks. The experiments on two public datasets show that our approach achieves higher accuracy than previous state-of-art methods. Our method reaches an accuracy of 85.11% and 78.46% on both parts of the ITOP dataset and an accuracy of 80.86% on the EVAL dataset.
Keywords: Edge Feature; Pose Regression Network; Depth Image